New therapeutic target for modulation of autophagy in osteoarthritis - Lui, Julian C. (Annals of Joint; Vol 3 (November 2018): Annals of Joint, 2018)
Autophagy is a normal intracellular mechanism for recycling unnecessary or dysfunctional cellular components and proteins, thus preserving energy and alleviating stress to promote cellular survival. Numerous recent studies have demonstrated the importance of autophagy in normal cartilage maintenance and implicated deregulation of autophagy in the pathogenesis of osteoarthritis (OA), which remains as the most common chronic joint disease and the leading cause of disability worldwide.